Conference of the Liber Groupe des Cartothecaires, Paris 29th August-2nd September 2006 - Richard, Helène (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
Following on from Copenhagen (2000), Helsinki (2002) and Cambridge (2004), the meeting of the "Groupe des Cartothécaires" took place in Paris from the 29th of August to the 2nd of September 2006. It was hosted by the Bibliothèque nationale de France ( BnF), with the support of Institut Géographique National ( IGN), Service Historique de la Défense ( SHD), Archives nationales and the Library of the Château de Chantilly. The Conference was organised by the Comité Français de Cartographie (CFC). A committee was set up within the CFC, which organised the scientific program and participated in the general organisation.